Molecular Dynamics Simulation of the Permeation of Lipid- Conjugated Peptides through the Stratum Corneum - Ruiz Perez, Lanie (Curtin University, 2021)
This thesis presents a significant advance in selection of drug candidates for transdermal drug delivery. The methodology uses molecular dynamics simulations to understand the translocation of drug candidates across a model of the skin barrier, in atomistic detail. With this, researchers can predict the translocation rate and efficiently shortlist the drug candidates before conducting costly laboratory-based trials. More importantly, predictions are made with high confidence due to the clarification of the molecular mechanism of translocation.